Relationships at Work: Integrating the Perspectives of Disability Partners to Enhance a Peer Navigation Intervention - Herrman, Deana; Papadimitriou, Christina; Green, Bob; LeFlore, Andrea; Magasi, Susan (Frontiers in Rehabilitation Sciences, 2022)
Objective: The Our Peers-Empowerment and Navigational Support (OP-ENS) community-based participation research study developed, implemented, and evaluated a peer navigator intervention aimed at improving health and healthcare access among Medicaid beneficiaries with disabilities. Peer navigators are community partners with disabilities trained to deliver structured peer support interventions that can address barriers to care. The purpose of this paper is two-fold. First, it explicates the relational work the peer navigators do with peers in delivering the intervention. Second, it illustrates how our community-based participatory approach empowered peer navigators to share their knowledge to refine the intervention. Methods: Clinical coordinator team meeting notes, critical incident documentation reports, peer navigator reflections (n=20) were analyzed thematically to understand the peer navigators’ relational work and intervention refinements. Following Labov’s 6-stage approach to personal narratives and a collaborative writing process academic, clinical, and disability partners co-wrote descriptive exemplars to showcase these processes. Findings: Through the manualized OP-ENS intervention process, peer navigators helped peers achieve incremental successes. Peer navigators used their training and personal experiences to engage with peers and forge deep connections and relationships of trust. As a result, peers identified a wide-range of social health concerns, including poverty, social isolation, and racial and disability related discrimination that might otherwise go unaddressed. True to the principles of community-based participatory research, by fostering an equity-focused collaboration and listening to peer navigators, the project team implemented subtle but salient refinements to the intervention. Refinements included an explicit focus on social determinants of health affecting peers’ health and well-being and supplemental trainings to help peer navigators support peers with significant mental health needs. Conclusion: The peer navigators were intentional and skilled at relationship building, thus complex elements which impact peers’ health were addressed. Peer navigators were empowered to communicate their perspectives with the study team, who worked together to strengthen the intervention processes and infrastructure. This atmosphere of trust and collaboration amongst diverse stakeholders was instrumental to OP-ENS' successful implementation. Healthcare systems should consider implementing peer support interventions that are responsive to consumer input to address social determinants of health for persons with disabilities.